Biomedical Engineering Systems and Technologies : 8th International Joint Conference, BIOSTEC 2015, Lisbon, Portugal, January 12-15, 2015, Revised Selected Papers - Fred, Ana.; Gamboa, Hugo.; Elias, Dirk.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2015, held in Lisbon, Portugal, in January 2015. The 27 revised full papers presented together with an invited paper were carefully reviewed and selected from a total of 375 submissions. The papers cover a wide range of topics and are organized in four general topical sections on biomedical electronics and devices; bioimaging; bioinformatics models, methods and algorithms; bio-inspired systems and signal processing; health informatics.
Biomedical electronics and devices -- Bioimaging -- Bioinformatics models, methods and algorithms -- Bio-inspired systems and signal processing -- Health informatics.
Keywords: Medical records -- Data processing; Bioinformatics; Computer vision; Biomedical engineering; Data mining; Health Informatics; Computational Biology/Bioinformatics.; Computer Imaging, Vision, Pattern Recognition and Graphics; Biomedical Engineering and Bioengineering; Data Mining and Knowledge Discovery